Penerapan Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) untuk Meningkatkan Kemampuan Penyelesaian Soal Cerita pada Kelas VII A SMP UTY - Idris, Invany; Silalahi, Desri Kristina (EduMatSains, 2016)
AbstractMathematical problem solving in the form of word problems is very helpful in dailystudent life because this problems always related to daily life. Problems encountered in this research, it was found that the students are less capable in solving word problems. This matterÂ  because students had not been given exercises in the form of word problems. To improve the students ability in solving word problems, researcherapply Indonesian Realistic Mathematics Education Approach (PMRI). This research aims to determine that the application PMRI approach can enhance the students ability in solving word problems and find out how the application PMRI in mathematic. This research is a classroom action research (CAR) conducted in SMP UTY, the Christian school located in t Medan. Based on the research results obtained, it is known that the application PMRI approach can enhance the students ability in solving word problems, although indicators of success has not been achieved in this study.